EPCO-01. EPIGENETIC REPROGRAMMING SHAPES THE MOLECULAR AND CELLULAR LANDSCAPE OF SCHWANNOMA. (14th November 2022) - John Liu, S; Casey-Clyde, Tim; Swinderman, Jason; Cho, Nam Woo; Vasudevan, Harish; Foster, Kyla; Pekmezci, Melike; Chen, William; Villanueva-Meyer, Javier; Hiam-Galvez, Kamir J; Swaney, Danielle; Choudhury, Abrar; et al.
Abstract: DNA methylation profiling provides robust classification of nervous system tumors, but mechanisms driving epigenetic identity of individual tumor types are incompletely understood. Integrating DNA methylation profiling (n=76), RNA sequencing (n=24), single-cell RNA-sequencing (n=9), and mass cytometry (n=9), we discovered vestibular schwannomas are comprised of two epigenetic groups distinguished by neural crest development pathways or repair and regeneration pathways driving immune infiltration. Analyses of preoperative magnetic resonance imaging studies (n=66) or paired primary and recurrent schwannomas (n=13) suggested radiotherapy was sufficient but not necessary for epigenetic reprogramming of neural crest enriched schwannomas into immune enriched schwannomas. In support of this hypothesis, DNA methylation profiling, RNA sequencing, single-cell RNA sequencing, proteomic mass spectrometry, and lymphocyte migration assays demonstrated radiotherapy epigenetically reprogramed viable schwannoma cells to secrete immunomodulatory signals and recruit lymphocytes in vitro . Genome-wide CRISPRi screens identified histone acetyltransferases or DNA methyltransferases driving schwannoma radiotherapy responses, including the epigenetic regulators KDM5C or KDM1A . CRISPRi and lymphocyte migration assays ± radiotherapy confirmed KDM5C drives schwannoma immune infiltration whereas KDM1A inhibits schwannoma immune infiltration. To define genomic mechanisms underlying epigenetic group identity, we performed pooled CRISPRi screening coupled with single-cell RNA sequencing (Perturb-seq) of 44 schwannoma markers. In parallel, we developed single nuclei profiling of chromatin accessibility through paired ATAC sequencing and RNA sequencing coupled with pooled CRISPRi screening (snARC-seq) of 54 epigenetic regulators identified by our genome-wide CRISPRi screen. Functional genomic approaches revealed the tyrosine phosphatase PTPRG as a regulator of survival, and KDM5C and KDM1A as regulators of inflammation. In summary, we report two epigenetic groups of schwannomas and mechanisms underlying epigenetic group identity using a new functional genomic technique allowing for simultaneous interrogation of single-cell epigenetic and gene expression changes in the context of genetic and therapeutic perturbations. These data elucidate a novel epigenetic mechanism of action of radiotherapy.